Constitutional Incoherence in Electoral Adjudication: An Analysis of Constitutional Court Decision No. 190/PHPU.D-VIII/2010 on Regional Election Violations and Substantive Justice - Muhammad Bagus Nurullah; Febrian Indar Surya Kusuma (Constitutionale, 2026)
This article examines the legal reasoning adopted by the Constitutional Court of the Republic of Indonesia in Decision Number 190/PHPU.D-VIII/2010 concerning the regional election dispute in Pandeglang Regency. It analyzes the Court's interpretation of electoral justice, the application of the structured, systematic, and massive (TSM) violations doctrine, and the evidentiary standards governing electoral disputes. The study aims to identify weaknesses in the Court's reasoning and reconstruct a more substantive constitutional approach that strengthens democratic integrity and protects political rights. Using normative and empirical legal methods, it applies statutory, conceptual, and case approaches supported by secondary empirical data from academic publications, legal journals, and public discussions on electoral dispute resolution in Indonesia. The findings show that the Court adopted a predominantly formalistic and quantitative approach by emphasizing vote differentials rather than the integrity of the democratic process. Strict evidentiary standards also hindered proof of violations involving intimidation, abuse of power, and political manipulation, limiting meaningful constitutional review. This article argues that electoral disputes should be treated not merely as procedural conflicts over vote tabulation but as constitutional issues involving democratic values, political equality, and public trust. It concludes that the Constitutional Court should adopt a more substantive and contextual model of constitutional reasoning to strengthen electoral justice and constitutional democracy in Indonesia.